Bibliometric Mapping of Halal Fashion Research Development With Scopus Index - Nadia Nurul Izza (SMART Insight, 2022)
According to the 2014 State of the Global Islamic Economy, the world's Muslim population of 1.6 billion people, or 25% of the world's population, has surpassed 7 billion. The Muslim population is scattered throughout numerous countries, and there are 56 Muslim-majority countries with a combined GDP of 6.7 trillion. Overall, the potential for Muslim consumers can be seen in the fact that global Muslim consumers' spending in the food and lifestyle sector is expected to exceed 3,7 trillion in 2019. This statistic represents a potential core market for the halal food and lifestyle sector. The growing Muslim population and purchasing power around the world, as well as the new period of modernization, support the trend of a rising halal lifestyles and Islamic trade. Sharia ideals will become increasingly prevalent as a way of life. Halal is viewed as a new trend for the 1.6 billion Muslim people. Global markets must respond to the distinct demands, preferences, and orientations of market and value economies, as well as trade economies. Halal lifestyle is a recent trend in Indonesia, and one aspect of it is the apparel sector or halal clothing. The purpose of this research is to discover the development map and trends of Halal Fashion as published by well-known publications in the field of Halal Industry. The data analyzed were more than 67 research publications indexed by Google Scholar. The export data is then processed and analyzed using the VOSviewer application program to find out the bibliometric map of the development of Halal Fashion. The results show that the number of publications on the development of the research role of the Halal Fashion continues to increase.